Intrapancreatic Accessory Spleen. A Case Report and Review of Literature - Katuchova, Jana; Baumohlova, Helena; Harbulak, Pavol; Stofcikova, Miloslava; Svajdler, Marian; Repovsky, Andrej; Radonak, Jozef (JOP. Journal of the Pancreas, 2013)
Context Accessory spleen is a congenital focus of healthy splenic tissue that is separated from the main body of spleen. Although an accessory spleen usually appears as an isolated asymptomatic abnormality, it may have clinical significance in some situations. Case report We report the case of 53-year-old woman with a 2-year history of upper abdominal discomfort after meals and weight loss. The pathologic lesion was diagnosed by the abdominal sonography and the magnetic resonance tomography in the pancreatic tail. The patient was operated with suspicion of a solid pseudopapillary neoplasm or a nonfunctioning islet cell tumor. Histopathological examination found an intrapancreatic accessory spleen, which is a congenital abnormality consisting of normal splenic tissue in ectopic sites. Conclusion We present possibilities of differential diagnosis of this entity. Image: Accessory spleen in the tail of pancreas.